Tax provision by international subsidiaries of Indian extractive industry multinationals: Do environmental pollution and corruption matter?. (January 2023) - Das, Khanindra Ch; Mahalik, Mantu Kumar; Sadorsky, Perry
Abstract: Outward foreign direct investment in the extractive industry increases the availability of metals and minerals that run the economic engine in the home country. It is unclear, however, whether tax provision by subsidiaries of emerging multinationals in extractive sectors respond to environmental pollution and corruption in the host country. In this paper we examine the tax provision in the host countries by subsidiaries of private sector based emerging multinationals in the extractive resources (metals and mining) sector. The analysis is carried out through a two-step system dynamic panel data GMM estimation, using data from 86 international subsidiaries of 15 Indian multinationals in 31 host countries for the period 2010 to 2019. Tax provisioning is found to be lesser in countries with higher environmental pollution. Tax provision is higher in countries with greater prevalence of corruption. However, the interactive effect suggests that in the presence of environmental pollution the subsidiary tax provisioning is higher in host countries if there is better control of corruption. This indicates that low corruption will offset a decline in tax provision from higher pollution. Furthermore, subsidiaries are found to have lesser tax provisioning when the parent firm has a tax dispute in the home country, implying the role of firm behaviour in shaping tax contribution by subsidiaries. The results are robust to the organization of subsidiaries through offshore financial centres. Highlights: Tax provision of Indian subsidiaries in extractive metals and minerals industry. In extractive industries tax provision by a multinational subsidiary is lower when environmental pollution is higher. In extractive industries tax provision by a multinational subsidiary is higher when corruption is higher. Corruption strengthens the negative relationship between pollution and the tax provision of a multinational subsidiary. Results are robust to the organization of subsidiaries through offshore financial centres.